Protecting or undermining the integrity of sport? The science and politics of the McLaren report - Girginov, V.; Parry, J. (International Journal of Sport Policy and Politics, 2018)
This study interrogates the ramifications for the integrity of sport of the McLaren Report (2016a McLaren, R., 2016a. The independent person report. Montreal: WADA, Available from: https://www.wada-ama.org/sites/default/files/resources/files/20160718_ip_report_newfinal.pdf [Accessed 3 January 2017]. [Google Scholar]) into doping allegations concerning the Sochi Olympics. Using an evidence-based approach to policymaking, the main claims of the report are subjected to scrutiny. The analysis suggests that McLaren`s report seriously undermines the integrity of Olympic sport for four main reasons: